2019
DOI: 10.1152/physrev.00055.2017
|View full text |Cite
|
Sign up to set email alerts
|

Thick Ascending Limb Sodium Transport in the Pathogenesis of Hypertension

Abstract: The thick ascending limb plays a key role in maintaining water and electrolyte balance. The importance of this segment in regulating blood pressure is evidenced by the effect of loop diuretics or local genetic defects on this parameter. Hormones and factors produced by thick ascending limbs have both autocrine and paracrine effects, which can extend prohypertensive signaling to other structures of the nephron. In this review, we discuss the role of the thick ascending limb in the development of hypertension, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 773 publications
(1,015 reference statements)
1
24
0
Order By: Relevance
“…The results of the 3-day ANG II simulations indicate that transporter abundance is not always a proxy for transporter flux. Activity per transporter can be modulated by local signals (nitric oxide, 20-HETE, dopamine, superoxide) that can override changes in transporter pool size (5,11), for example, by stimulating trafficking into and out of active domains in the plasma membrane (24). Lack of correlation between overall abundance and transport capacity is also evident in ENaC activation mediated by subunit cleavage, which is associated with apparent decreases in pool size of full-length subunits with the appearance of pools of smaller subunits (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the 3-day ANG II simulations indicate that transporter abundance is not always a proxy for transporter flux. Activity per transporter can be modulated by local signals (nitric oxide, 20-HETE, dopamine, superoxide) that can override changes in transporter pool size (5,11), for example, by stimulating trafficking into and out of active domains in the plasma membrane (24). Lack of correlation between overall abundance and transport capacity is also evident in ENaC activation mediated by subunit cleavage, which is associated with apparent decreases in pool size of full-length subunits with the appearance of pools of smaller subunits (43).…”
Section: Discussionmentioning
confidence: 99%
“…Cowley (5) summarized the many studies indicating that depression of mTAL Na ϩ transport plays a key role in driving pressure natriuresis (as evident during ANG II hypertension), specifically mediated by changes in medullary blood flow driven by renal interstitial hydrostatic pressure and in medullary redox state influenced by nitric oxide production. The regulation of NKCC2 along the TAL was recently reviewed by Gonzalez-Vicente et al (11), who concluded that the effects of ANG II on Na ϩ transport in this region, including the mediating signaling cascades, are not well understood.…”
Section: K + Excretionmentioning
confidence: 99%
“…Na + regulation has been previously reported at several nephron segments mediated by agents such as NO and angiotensin II in the cTAL [4,5], NO and arginine vasopressin at the cortical collecting duct level [6], and other segments [7]. The final effect of the interaction between NO and 8-iso-PGF2α is based on the intracellular activation of different regulators.…”
Section: Introductionmentioning
confidence: 85%
“…Effects of rings fusion on basicity and aromaticity were analyzed for neutral, deprotonated, protonated, and cationized forms. For complexes with M + , we chose the two smallest alkali metal cations, Li + and Na + , effects of which on human organisms, particularly on central nervous and cardiovascular systems and on metabolic functions and nucleic acids chemistry, have been discussed in the literature [54][55][56][57][58]. Their noncovalent interactions with some amino acids, peptides, sugars, and nucleobases have also been signaled [59][60][61][62][63].…”
Section: Methodsmentioning
confidence: 99%